The role of ornament in shaping architectural space on the example of stucco decorations attributed to the workshop of Giovanni Battista Falconi - Klimek, Beata (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
The article presents the role played by selected types of stucco ornaments in shaping the interior spaces they decorate. Characteristic types of ornaments found in stucco in the 17th century in Małopolska were described. Decorative and multiple ornament is subordinated to the types of vaults decorated with interiors. To illustrate these connections, ornaments used in stucco decorations attributed to the workshop of Giovanni Battista Falconi were used.